2020
DOI: 10.1109/tit.2020.2977631
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the Length of Functional PIR and Batch Codes

Abstract: A functional k-PIR code of dimension s consists of n servers storing linear combinations of s linearly independent information symbols. Any linear combination of the s information symbols can be recovered by k disjoint subsets of servers. The goal is to find the smallest number of servers for given k and s. We provide lower bounds on the number of servers and constructions which yield upper bounds on this number. For k ≤ 4, exact bounds on the number of servers are proved. Furthermore, we provide some asymptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The binary k × n matrix G (as well as the binary linear code generated by G) is (i) a t-PIR code, (ii) a t-batch code, (iii) a t-odd batch code, or (iv) a t-functional batch code if G can serve any request sequence of length t consisting of (i) the t-fold repetition of a unit vector in E k , (ii) unit vectors in E k only, (iii) vectors in F k 2 of odd weight only, or (iv) nonzero vectors in F k 2 , respectively. The notions of t-PIR code and t-batch code are well known (but note that some authors employ a more general definition and refer to these codes as multiset primitive), and together with t-functional batch codes are defined, for example, in [15,16]. For a recent overview of these and related types of codes, see [7].…”
Section: Definition 22mentioning
confidence: 99%
See 3 more Smart Citations
“…The binary k × n matrix G (as well as the binary linear code generated by G) is (i) a t-PIR code, (ii) a t-batch code, (iii) a t-odd batch code, or (iv) a t-functional batch code if G can serve any request sequence of length t consisting of (i) the t-fold repetition of a unit vector in E k , (ii) unit vectors in E k only, (iii) vectors in F k 2 of odd weight only, or (iv) nonzero vectors in F k 2 , respectively. The notions of t-PIR code and t-batch code are well known (but note that some authors employ a more general definition and refer to these codes as multiset primitive), and together with t-functional batch codes are defined, for example, in [15,16]. For a recent overview of these and related types of codes, see [7].…”
Section: Definition 22mentioning
confidence: 99%
“…In [9] (see also [10]) it was shown that G k is a 2 k−1 -batch code, but the proof is somewhat cumbersome. Recently, it was conjectured that G k is even a 2 k−1 -functional batch code, and it was shown that G k is a t-functional batch code for t = 2 k−2 + 2 k−4 + ⌊2 k/2 / √ 24⌋, again with a rather involved proof [15,16]. After completion of this paper, we learned that this result was further improved in [13] and [12], where it was shown that G k is a t-functional batch code for t = ⌊(2/3) • 2 k−1 ⌋ and t = ⌊(5/6) • 2 k−1 ⌋ − k, respectively.…”
Section: Definition 22mentioning
confidence: 99%
See 2 more Smart Citations
“…The case of maximum distance separable (MDS) coded servers was considered in [11], [12], while the case of arbitrary linear coded servers was studied in [13]- [15]. The concept of PIR has also been extended to several other relevant scenarios, which include colluding servers [11], [13], [15]- [19], robust PIR [16], PIR with Byzantine servers [20], optimal upload cost of PIR, i.e., the minimum required amount of query information [21], access complexity of PIR, i.e., the number of symbols accessed across all servers for the retrieval of a single file [22], single-server PIR with private side information [23], PIR on graph-based replication systems [24], PIR with secure storage [25], functional PIR codes [26], and private proximity retrieval codes [27].…”
Section: Introductionmentioning
confidence: 99%